PERUMUSAN STRATEGI PEMASARAN DI PT GERBANG SARANABAJA DENGAN MATRIKS IFE & EFE - Simangunsong, Putri Cornellia Theresia; Alamsyah, Nanang (Academy of Education Journal, 2023)
The number of local and international competitors makes companies engaged in the manufacturing industry required to be able to survive to achieve the desired goals. Therefore, the authors are interested in conducting research on companies engaged in manufacturing and construction services at PT Gerbang Saranabaja. PT Gerbang Saranabaja is a company in the form of a Limited Liability Company (PT) engaged in steel construction. The method used in this research is qualitative method. To find out the company's weaknesses and strengths, the authors use the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. The score for IFE is 3.90 and the score for EFE is 2.99, so that from the SPACE Matrix it can be seen that PT Gerbang Saranabaja is in a highly unprofitable condition. The results of an IE score of 3.90 and an EFE score of 2.99 were also obtained, so that PT Gerbang Saranabaja is in quadrant IV, namely with highly unprofitable conditions.